An investigation into the lateral loading response of shallow bucket foundations for offshore wind turbines through centrifuge modeling in sand. (June 2019) - Ma, Pengcheng; Liu, Run; Lian, Jijian; Zhu, Bin
Highlights: The deformation pattern of the shallow buried foundation is revealed through the analysis of loading-displacement relationship and the distribution of pore pressures and soil pressures of centrifuge tests. The pore pressure accumulation of the sandy ground inside the bucket due to the long-term cyclic loading is revealed by the analysis of the centrifuge tests, and the accumulation of pore pressure has the effect on decreasing the anti-overturning bearing capacity of shallow bucket foundation. The easy-to-use analytical equations via limit equilibrium, considering the effect of long-term cyclic loading and the deformation pattern of shallow bucket foundation, are proposed to assess the anti-overturning bearing capacity of shallow bucket foundations. Abstract: A shallow suction bucket is a new foundation type for offshore wind turbines. Due to its large size and bulky shape, the bucket and the soil within the bucket do not necessarily deform as a whole. Moreover, limited research has been conducted on the hydrodynamic wave influence on the shallow bucket bearing response. These factors pose great challenges to the shallow bucket foundation design. This paper presents a set of centrifuge tests of a shallow bucket model subjected to monotonic and dynamic lateral loads to study the lateral bearing response of shallow bucket foundations in the field under combined loads induced by wind, waves, etc. In addition to the routine measurements ( e.g., load-displacement), the soil pressures on the bucket and the distribution and evolution of the excess pore pressures in the surrounding soils are also obtained. The deformation pattern of the bucket ( e.g., rotation center) is revealed through displacement measurements. Finally, the proposed easy-to-use analytical equations using the limit equilibrium to assess the bearing capacity of bucket foundations, taking into account the influence of the soil strength degradation caused by hydrodynamic wave loadings, are found to yield good results upon comparison with the centrifuge data, providing useful guidelines for the design of shallow bucket foundations.